The determinants of stock prices: a new evidence from 2003 to 2016 - MENG, XIN (2017)
The question studied in this dissertation is about the determinants of stock prices in European area covering the period from 2003 to 2016. On the basis of daily stock price data, the dataset is established, which contains 124 companies listed on the three major index in Europe: FTSE 100 Index, DAX Index, CAC 40 Index. It tests eight typical determinant variables: interest rates, exchange rates, dividend yields, price earnings ratios, long term price earnings ratios, book value, price to book ratios and capital expenditures.